An intrinsic value system for developing multiple invariant representations with incremental slowness learning - Luciw, Matthew D.; Kompella, Varun R.; Kazerounian, Sohrob; Schmidhuber, Jürgen (Frontiers in Neurorobotics, 2013)
Curiosity Driven Modular Incremental Slow Feature Analysis (CD-MISFA; cdmisfa) is a recently introduced model of intrinsically-motivated invariance learning, which shows how curiosity enables the orderly formation of multiple stable sensory representations, through which the agent can simplify its complex sensory input. Here, we first discuss the computational properties of the CD-MISFA model itself, followed by a discussion of neurophysiological analogs fulfilling similar functional roles. CD-MISFA combines 1. unsupervised representation learning through the slowness principle, 2. generation of an intrinsic reward signal through the learning progress of the developing features, and 3. balancing of exploration and exploitation in order to maximize learning progress and quickly learn multiple feature sets for perceptual simplification. Experimental results on synthetic observations and on the iCub robot show that the intrinsic value system is an essential component to representation learning, further, the model explores such that the representations are typically learned in order from least to most costly, as predicted by the theory of Artificial Curiosity.